2022
DOI: 10.3390/ijms23042171
|View full text |Cite
|
Sign up to set email alerts
|

Implication of COVID-19 on Erythrocytes Functionality: Red Blood Cell Biochemical Implications and Morpho-Functional Aspects

Abstract: Several diseases (such as diabetes, cancer, and neurodegenerative disorders) affect the morpho-functional aspects of red blood cells, sometimes altering their normal metabolism. In this review, the hematological changes are evaluated, with particular focus on the morphology and metabolic aspects of erythrocytes. Changes in the functionality of such cells may, in fact, help provide important information about disease severity and progression. The viral infection causes significant damage to the blood cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 124 publications
(155 reference statements)
3
49
0
1
Order By: Relevance
“…Viral infections can affect red blood cells, changing their size, firmness and distribution width. This change was also detected in patients with COVID-19 and was associated with the severity of the disease (17). RDW-SD and MCV were associated with mortality, while Hb and HCT were not in the study of Pluta et al (18) including 70 patients who were admitted to the ICU with COVID-19.…”
Section: Discussionmentioning
confidence: 80%
“…Viral infections can affect red blood cells, changing their size, firmness and distribution width. This change was also detected in patients with COVID-19 and was associated with the severity of the disease (17). RDW-SD and MCV were associated with mortality, while Hb and HCT were not in the study of Pluta et al (18) including 70 patients who were admitted to the ICU with COVID-19.…”
Section: Discussionmentioning
confidence: 80%
“…SARS-CoV-2 attacking facilitates iron removal from the heme prosthetic group, which leads to the loss of functional haemoglobin. 38 , 39 The authors found that oxidative stress connected with COVID-19 damages essential proteins in erythrocytes, including those that influence membrane structure and the ability to transport and deliver oxygen. Because mature erythrocytes cannot synthesize new proteins to replace damaged ones and the average lifespan of erythrocytes is 120 days, the authors hypothesize that the circulation of irreversibly damaged erythrocytes with impaired function could contribute to the long-term effects of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is regarded as a docking site for structural proteins necessary for membrane integrity [52] and is mandatory for oxygen release and metabolic processes [51]. Thus, SARS-CoV-2 spike protein binding to RBC Band3 protein disturbs oxygen transport function causing severe hypoxia and metabolic alterations that increase the risk of RBC injury and hemolytic effect [13,51]. Band3 protein inhibits glycolytic enzyme function during normal oxygen saturation.…”
Section: Sars-cov-2 and Direct Erythrocytes Injurymentioning
confidence: 99%
“…Given the known risk of thrombosis in patients with cold agglutinin hemolytic anemia, Maslov et al (2020) speculated that this might contribute to thrombosis and the unfavorable outcomes in COVID-19 patients [12]. The hemolysis of RBCs may also be caused by impairment of their morphology and functionality due to the virus infection [13], which is critical in cases of hemoglobinopathies or inherited anemias [14]. Severance et al revealed that induction of hemolytic anemia in children with hereditary spherocytosis is due to provoking oxidative stress by SARS-CoV-2 infection [15].…”
Section: Introductionmentioning
confidence: 99%